Pengaruh Pola Asuh dan Komunikasi Orang Tua terhadap Sikap Sosial Siswa Kelas Atas SD Muhammadiyah Baturan Tahun Ajaran 2015/2016 - Maulana, Novika; , Dra.Ratnasari Diah Utami, M.Si.,M.Pd (2016)
The aim of study was to determine the impacts of: (1) parenting style on student's social attitude of high grade SDM Baturan. (2) Parenting communication on student's social attitude of high grade SDM Baturan. (3) Parenting style and communication on student's social attitude of high grade SDM Baturan. This research was analytic survey research which used kind statistical data for analysed data. The population are all high grade at SDM Baturan totaling 59 student, the sample are 30 student. The techniques of collecting data used questionnaire, documentation and interview. The data analysis technique used multiple linier regression, ttest, Ftest, the coefficient of determination, relative contribution, effective contribution preceded by analysis prerequisite test are normaly test and linierity test. Based on analysis result can concluded: (1) parenting style effect on student's social attitude. Based on t test result: tcount > ttable is 2.112 > 2.048 and the significance value < 0.05 is 0.044. (2) Parenting communication effect on student's social attitude. Based on t test result: tcount > ttable is 3.203 > 2.048 and the significance value < 0.05 is 0.003. (3) parenting style and communication effect on student's social attitude. Based on F test result: Fcount > Ftable is 9.561 > 3.32 and the significance value < 0.05 is 0.001.